Redeeming Our Thinking About History: A God-Centered Approach - Larson, Olle T. (Trinity journal, 2023)
Review of Poythress, Vern S. Redeeming Our Thinking About History: A God-Centered Approach. Publisher: Wheaton, IL : Crossway, 2022. ISBN: 978-1-4335-7144-2